Fish fauna from a fragmented river in the Atlantic Forest - Brito, Paulo Roberto Monteiro de; Pereira, Luiz Henrique Garcia; Roxo, Fábio Fernandes [UNESP]; Monteiro, Jefferson Henriques [UNESP]; Oiveira, Claudio; Silva, Guilherme José da Costa [UNESP] (FapUNIFESP (SciELO), 2022)
This study sought to identify the ichthyofauna composition of the Muzambinho River, an upland tributary of the Paraná River. We also investigate whether waterfalls in the region can serve as barriers to the dispersal of fish species. For this purpose, collections were carried out at 34 points on the Muzambinho River using different techniques. In all, 37 species were recorded, some of which were endemic, and the majority were native. Among these species, some are predominant in degraded places and can be used as bioindicators. The results also demonstrate zonation in the ichthyofauna composition in Muzambinho that segregates the fauna into three sessions separated by waterfalls: Lower Muzambinho, Upper Muzambinho, and Sao Domingos. We conclude that, for the ideal preservation of the ichthyofauna of the Muzambinho River, it is necessary to preserve its sections independently, which would guarantee the maintenance of naturally isolated strains.
Fauna de peixes de um rio fragmentado na Mata Atlântica
Keywords: Biodiversity; Ictiofauna; Mantiqueira; Upper Parana